2002
DOI: 10.1021/ol026230v
|View full text |Cite
|
Sign up to set email alerts
|

First Asymmetric Total Synthesis of (+)-Sparteine

Abstract: [reaction: see text] The total synthesis of (+)-sparteine was accomplished from 2,5-norbornadione in 15 steps and 15.7% overall yield. The key steps were two ring-expansion reactions, one involving an intramolecular Schmidt reaction and one using a novel variant of the photo-Beckmann rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 14 publications
1
84
0
Order By: Relevance
“…[20Ϫ23] However, the preparation of enantiopure α-aminoalkyltriorganotins as potential precursors of enantiopure α-amino anions upon transmetallation with nbutyllithium appears to offer great potential [24,25] and initiated our investigations into the synthesis of N-protected 2-triorganostannyl-1,3-oxazolidines. The advantage of this approach in comparison with enantioselective deprotonation by n-butyllithium or sec-butyllithium in the presence of (Ϫ)-sparteine [26Ϫ30] , (ϩ)-sparteine [31] or a (ϩ)-sparteine surrogate derived from cytisine [32] should be the obtaining of chiral α-aminoorganolithium reagent uncomplexed with a diamine ligand. Accordingly, an efficient route to provide 2-triorganostannyl-1,3-oxazolidines selectively would seem to be of great interest in order subsequently to provide chiral α-aminoorganostannanes through ring opening of the oxazolidine component.…”
Section: Introductionmentioning
confidence: 99%
“…[20Ϫ23] However, the preparation of enantiopure α-aminoalkyltriorganotins as potential precursors of enantiopure α-amino anions upon transmetallation with nbutyllithium appears to offer great potential [24,25] and initiated our investigations into the synthesis of N-protected 2-triorganostannyl-1,3-oxazolidines. The advantage of this approach in comparison with enantioselective deprotonation by n-butyllithium or sec-butyllithium in the presence of (Ϫ)-sparteine [26Ϫ30] , (ϩ)-sparteine [31] or a (ϩ)-sparteine surrogate derived from cytisine [32] should be the obtaining of chiral α-aminoorganolithium reagent uncomplexed with a diamine ligand. Accordingly, an efficient route to provide 2-triorganostannyl-1,3-oxazolidines selectively would seem to be of great interest in order subsequently to provide chiral α-aminoorganostannanes through ring opening of the oxazolidine component.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Amide reduction completed the synthesis of (À)-sparteine,which was isolated as the bisulfate salt, [24] after recrystallization, in 67 %yield. [25] Theoptical rotation (of the free base,[ a] D = (À)20.4 (c = 1.0, EtOH);l it., [17] [a] D = (À)20.7 (c = 1.8, EtOH)) confirmed that (À)-sparteine had been synthesised. Overall, this diastereocontrolled synthesis of (À)-sparteine was completed in 10 steps (longest linear sequence [23] )i n3 1% yield.…”
mentioning
confidence: 72%
“…[13] Over the years,our group [10,14] and others [15] have explored synthetic approaches to enantiopure (+ +)-and (À)-sparteine surrogate.However,all approaches are either inconveniently long,lack diastereo-and/or regioselectivity,only allow access to one enantiomer,a nd/or proceed with overall low yields. These limitations have thus far precluded the synthesis of enantiopure (+ +)-and (À)-sparteine surrogate on agram-scale and addressing this is the primary topic of this paper.I n addition, in designing our new approach to the sparteine surrogate,w er ecognized that it could also be adapted to deliver an ew resolution/reconnection strategy for the gramscale synthesis of (À)-sparteine.Despite numerous syntheses of racemic sparteine over 65 years, [16] there are only two enantioselective syntheses (by AubØ [17] and our group [18] ), which delivered around 50 mg quantities of (+ +)-or (À)-sparteine over long or low-yielding approaches.…”
mentioning
confidence: 99%
“…However, the original synthesis was challenging because the precursor (R,R)-1-BH 3 had to be prepared with (+)-sparteine. 137 The problem was solved by the development of another reaction route. Scheme 2 shows the new synthetic route to obtain both (S,S)-3-BH 3 and (R,R)-3-BH 3 from 5-BH 3 with the only (− )-sparteine.…”
Section: P-stereogenic Cyclic Phosphines For Chiral Element-blocksmentioning
confidence: 99%